MANAGEMENT AND OUTCOME OF JAUNDICE SECONDARY TO MALIGNANCIES OF THE GALL BLADDER, BILIARY TREE AND PANCREAS: A SINGLE CENTRE EXPERIENCE - Salim, Adnan; Jabbar, Sadia; ul Amin, Farhan; Malik, Kashif (Journal of Ayub Medical College Abbottabad, 2018)
Background: Obstructive jaundice due to malignancies of the biliary tree, gall bladder and pancreas account for a significant number of patients managed by tertiary centres. Management options are curative or palliative, depending on disease stage. This study was performed to see the effectiveness of treatment modalities for these patients and eventual outcome. Methods: This cross-sectional analytical study was conducted at the Department of Gastroenterology and Hepatology, Shaikh Zayed Hospital Lahore, from January 2015 to June 2016. All adult patients aged 18 and above of either sex presenting with obstructive jaundice secondary to malignant disease originating from the gallbladder, biliary-tree or pancreas were included in the study. The disease was staged after admission. The patients then underwent endoscopic, surgical or percutaneous drainage and were followed up for a period of one year. Results: two hundred & sixty-two patients presenting with jaundice due to malignancy arising from the biliary tree, gall bladder or pancreas were enrolled between January 2015 and June 2016, 141 (53.8%) males and 121 (46.2%) females. Eighty (30.5%) had cholangiocarcinoma, 70 (26.7%), had gall bladder tumours, 61 (23.3%) pancreatic cancer and 51(19.5%) had ampullary tumours. 31 (11.8%) patients had disease qualifying curative surgical resection. One hundred & eighty-five (70.6%) patients underwent palliative therapy in the form of percutaneous in 86 (32.9%) and endoscopic drainage in 126 (48.1%). Twenty-eight (10.7%) patients refused all treatment. Eighteen (6.9%) patients died before undergoing any therapeutic intervention. Thirty-three (12.6%) died during hospital stay. Survival at 3, 6 and 12 months was 49.2% (129 patients), 28.2% (74 patients) and 8.4% (22 patients), respectively. These 22 included all patients who had underwent curative resection. We attributed the largest number of deaths, 197 (75.2%) patients, to metastatic/advanced disease and associated complications. Conclusion: The results showed that patients with advanced disease who were only eligible for palliative therapy, at first presentation, constituted the majority of patients. These patients require skilled endoscopy and interventional radiology teams for successful biliary drainage. Keywords: Gall bladder tumour; cholangiocarcinoma; ampullary tumour; pancreatic tumour; obstructive jaundice; ultrasound; CT scan; ERCP; percutaneous biliary drainage